Curcumin-Mediated HDAC Inhibition Suppresses the DNA Damage Response and Contributes to Increased DNA Damage Sensitivity - Wang, Shu-Huei (PLoS One, 2015)
Chemo- and radiotherapy cause multiple forms of DNA damage and lead to the death of cancer cells. Inhibitors of the DNA damage response are candidate drugs for use in combination therapies to increase the efficacy of such treatments. In this study, we show that curcumin, a plant polyphenol, sensitizes budding yeast to DNA damage by counteracting the DNA damage response. Following DNA damage, the Mec1-dependent DNA damage checkpoint is inactivated and Rad52 recombinase is degraded by curcumin, which results in deficiencies in double-stand break repair. Additive effects on damage-induced apoptosis and the inhibition of damage-induced autophagy by curcumin were observed. Moreover, rpd3 mutants were found to mimic the curcumin-induced suppression of the DNA damage response. In contrast, hat1 mutants were resistant to DNA damage, and Rad52 degradation was impaired following curcumin treatment. These results indicate that the histone deacetylase inhibitor activity of curcumin is critical to DSB repair and DNA damage sensitivity.